1991
DOI: 10.1210/mend-5-9-1339
|View full text |Cite
|
Sign up to set email alerts
|

Independent Expression of the α and β c-erbA Genes in Developing Rat Brain

Abstract: Thyroid hormone is important for normal brain development. Cellular responses to thyroid hormone are mediated by multiple nuclear receptors, classified into alpha- and beta-subtypes. In the rat, expression of both the alpha and beta genes results in several translation products. By using cRNA probes common to alpha transcripts or specific for alpha-1 and beta-1, we have studied the distribution of these transcripts in rat brain at different stages of development from embryonic day 14 to adult age by using in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(98 citation statements)
references
References 0 publications
7
91
0
Order By: Relevance
“…In contrast, hr is predominantly expressed in brain and skin (11,13), and Hr binds to only one (TR) of several steroid and retinoid receptors tested. Hr and TR are both nuclear proteins and are coexpressed in various regions of the brain (11,33,34), suggesting that the interaction observed in vitro also occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, hr is predominantly expressed in brain and skin (11,13), and Hr binds to only one (TR) of several steroid and retinoid receptors tested. Hr and TR are both nuclear proteins and are coexpressed in various regions of the brain (11,33,34), suggesting that the interaction observed in vitro also occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the specificity of interaction between TR and Hr, Hr In addition to their interaction in vitro, Hr and TR are expressed in the same cell types in vivo. We have shown previously that hr is expressed in tissues that express TR; in situ hybridization analyses have shown that hr and TR transcripts are present in the same cell populations in the brain (11,33,34). For interaction of Hr and TR to occur in vivo, both must occupy the same subcellular compartment.…”
Section: Expression Of Hr Is Directly Regulated By Thyroid Hormonementioning
confidence: 99%
“…When grafted in vivo, or when deprived of serum, they stop proliferating and differentiate into neuron-like cells within 1 wk. C17.2 cells probably originate from the cerebellum external granular layer, a transient structure populated by granular neuron precursors, and like these natural progenitors, express few if any TRs (30)(31)(32). We transfected these cells to express in a stable manner either TRα1 or TRβ1 and the reporter enhanced green fluorescent protein (Fig.…”
mentioning
confidence: 99%
“…TR␣ and TR␤ are produced in the CNS, but their patterns of expression vary markedly according to developmental stages, cell phenotype, and intracerebral localization (Bradley et al, 1989(Bradley et al, , 1992Strait et al, 1990Strait et al, , 1991Mellström et al, 1991;Puymirat et al, 1991;Puymirat, 1992;Lechan et al, 1993;Carré et al, 1998). Notably they were not detected in all neurons or macroglial cells (Puymirat et al, 1991;Puymirat, 1992).…”
mentioning
confidence: 99%